2021
DOI: 10.3389/fnut.2021.762383
|View full text |Cite
|
Sign up to set email alerts
|

Beverages Consumption and Oral Health in the Aging Population: A Systematic Review

Abstract: Little study has yet been made of the effect of different beverages on oral health outcomes in the aging population. The purpose of this systematic review is to evaluate the association between different beverages, including alcohol intake, coffee, milk, tea, and sugary drinks, and a cluster of oral health outcomes, including periodontal disease, oral dysbiosis, and tooth loss in older adults. The literature was screened from the inception up to May 2021 using six different electronic databases. Two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
(84 reference statements)
0
34
1
Order By: Relevance
“…The oral cavity is the first organ of the body to come in contact with coffee, and residual coffee components in the oral cavity after drinking may affect the health of periodontal tissues. Most studies have confirmed the benefits of coffee consumption in periodontal health [ 23 , 35 , 36 , 37 , 38 ]. In addition, CGA in coffee has a direct inhibitory effect on P. gingivalis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is the first organ of the body to come in contact with coffee, and residual coffee components in the oral cavity after drinking may affect the health of periodontal tissues. Most studies have confirmed the benefits of coffee consumption in periodontal health [ 23 , 35 , 36 , 37 , 38 ]. In addition, CGA in coffee has a direct inhibitory effect on P. gingivalis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically speaking, aging occurs with a pattern of sensory decline [ 3 , 34 ], translating into reduced appetite and sensory perception, which are well-known dimensions underlying frailty, sarcopenia, and physical decline [ 35 , 36 ]. This sensory deficiency carries serious implications for safety, nutrition, quality of life, and social relationships [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the recent replacement of cream with skimmed milk powder in the coffee mix is thought to be helpful in preventing osteoporosis, thus can also be protective against periodontal bone loss. 10,18 Milk belongs to dairy products, with calcium and casein content that is helpful in bone and tooth mineral preservation. 18 Other explanation of the coffee protective effect against alveolar bone loss is also presented by Ng et al It was stated that caffeine has immunomodulatory actions by inhibiting cyclic adenosine monophosphatase (cAMP)-phospodiesterase, thus increasing the concentration of intracellular cAMP.…”
Section: Key Findingsmentioning
confidence: 99%
“…10,18 Milk belongs to dairy products, with calcium and casein content that is helpful in bone and tooth mineral preservation. 18 Other explanation of the coffee protective effect against alveolar bone loss is also presented by Ng et al It was stated that caffeine has immunomodulatory actions by inhibiting cyclic adenosine monophosphatase (cAMP)-phospodiesterase, thus increasing the concentration of intracellular cAMP. 9 Another supporting result was also presented by Machida et al that observed the effect of consuming coffee during the maintenance phase of periodontal therapy.…”
Section: Key Findingsmentioning
confidence: 99%